Determinants of Employee Whistleblowing Intentions in Indonesia: Applying Theory of Planned Behavior - Nurul Mustafida (The Indonesian Journal of Accounting Research, 2020)
This study examines the effect of factors in the theory of planned behavior on whistleblowing intentions which are moderated by perceived organizational support. This study uses an online survei method with 155 samples of company employees. The research data are analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach, which used a measurement model and a structural model. The result shows that attitude and perceived subjective norms significantly and positively affect whistleblowing intentions. However, perceived behavioral control does not significantly affect whistleblowing intention due to fear of retaliation for the act of fraudulent financial reporting. Furthermore, the result indicates that perceived organizational support strengthens the positive relationship between attitude and perceived subjective norms with whistleblowing intentions, but does not have a moderating effect on the relationship of perceived behavioral control with whistleblowing intentions. This result implies that organizational support can encourage employees to enforce organizational rules and ethics. Besides, it shows employee’s feel valued and cared for in the organization so that it has positive implications, namely high commitment to the organization.